Responding to the 'Weight of the World': Unveiling the 'Feeling' Bourdieu in Social Work. (2nd August 2021) - Houston, Stan; Swords, Calvin
Abstract: The world continues to lurch from crisis to crisis. Amidst environmental decline, growing disparities in wealth and social dislocation, a minority of the world's population ironically prosper while the silent majority struggle to maintain basic standards of economic and social well-being. Social workers are compelled to respond to societal issues such as these but need theories to make sense of disparities in lived experience and life outcomes. Responding to this necessity, some social work scholars have drawn on Pierre Bourdieu's meta-theory to explain social injustice and guide anti-oppressive practice. While this growing corpus of work is encouraging, further critical appraisal of Bourdieu's work is required. In this article, we identify a gap in Bourdieu's meta-theory: the relative inattention to human affect and how it connects with his formative concepts of 'habitus', 'field' and 'capital'. This focus on human affect is salutary given its centrality in social work practice. To address this gap, we proffer some tentative thoughts about the nature of 'affective habitus', 'affective fields' and 'affective capital'. The implications of these enriched concepts for social work are finally considered. Abstract : This article builds on the application of Pierre Bourdieu's ideas for social work. It highlights a gap in Bourdieu's work: his lack of attention to emotion. This gap is addressed by applying emotional considerations to his lead concepts of habitus, field and capital. The implications for social work are then considered.